Voluntary wheel exercise training affects locomotor muscle, but not the diaphragm in the rat - Borzykh, Anna A.; Gaynullina, Dina K.; Shvetsova, Anastasia A.; Kiryukhina, Oxana O.; Kuzmin, Ilya V.; Selivanova, Ekaterina K.; Nesterenko, Alexey M.; Vinogradova, Olga L.; Tarasova, Olga S. (Frontiers in Physiology, 2022)
Introduction: Functional tests and training regimens intensity-controlled by an individual are used in sport practice, clinical rehabilitation, and space medicine. The model of voluntary wheel running in rats can be used to explore molecular mechanisms of such training regimens in humans. Respiratory and locomotor muscles demonstrate diverse adaptations to treadmill exercise, but the effects of voluntary exercise training on these muscle types have not been compared yet. Therefore, this work aimed at the effects of voluntary ET on rat triceps brachii and diaphragm muscles with special attention to reactive oxygen species, which regulate muscle plasticity during exercise. Methods: Male Wistar rats were distributed into exercise trained (ET) and sedentary (Sed) groups. ET group had free access to running wheels, running activity was continuously recorded and analyzed using the original hardware/software complex. After 8 weeks, muscle protein contents were studied using Western blotting. Results: ET rats had increased heart ventricular weights but decreased visceral/epididymal fat weights and blood triglyceride level compared to Sed. The training did not change corticosterone, testosterone, and thyroid hormone levels, but decreased TBARS content in the blood. ET rats demonstrated higher contents of OXPHOS complexes in the triceps brachii muscle, but not in the diaphragm. The content of SOD2 increased, and the contents of NOX2 and SOD3 decreased in the triceps brachii muscle of ET rats, while there were no such changes in the diaphragm. Conclusions: Voluntary wheel running in rats is intensive enough to govern specific adaptations of muscle fibers in locomotor, but not respiratory muscle.